Formulation and Evaluation of Liquid based Supersaturable Selfnanoemulsifying Drug Delivery System of Manidipine (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The aim of current research is to develop a liquid supersaturable self-nanoemulsifying drug delivery system (S-SNEDDS) of manidipine for enhancing the solubility and dissolution rate. Cithrol GMS – Cerex ELS250 – Propylene Glycol laurate are chosen based on the maximum solubility of manidipine and were used to construct ternary phase diagrams with Smix in 3:1 ratio and 20 mg drug loading was done and evaluated for entrapment efficiency, drug content and in-vitro drug release. To choose a precipitation inhibitor, in-vitro precipitation studies were carried out, and supersaturable SNEDDS were made the prepared formulations were evaluated and final optimised one is characterised for FTIR, SEM, globule size, zetapotential and stability studies. Out of all formulation F14 exhibited good results with highest drug content of 98.45±1.39% and entrapment efficiency of 98.91±1.70 % and drug release of 98.21% in 60min. F14 with PVP K17 (2%) precipitation inhibitor (SF14) exhibited drug content of 99.05% and entrapment efficiency was 99.75% which was almost >1% higher when compared to manidipine SNEDDS (F14). Manidipine S-SNEDDS (SF14) had the maximum drug release (99.85%) in 60min. SF14 S-SNEDDS had a mean globule size of 162.3 nm and zeta potential (mean) values ranged between -13.1 mV. The FT-IR, SEM and stability studies confirmed the complexation of manidipine and amorphous state of the drug and formulation to be stable for 3 months. Thus, this study indicated that the solid SNEDDS could be used as a potential drug carrier for manidipine with improved solubility and dissolution rate.